Design and Evaluation of S-Protected Thiolated-Based Itopride Hydrochloride Polymeric Nanocrystals for Functional Dyspepsia: QbD-Driven Optimization, In Situ, In Vitro, and In Vivo Investigation - Moutaz Y. Badr; Pratap Basim; Khaled M. Hosny; Waleed Y. Rizg; N. Raghavendra Naveen; Mallesh Kurakula; Fayez Alsulaimani; Awaji Y. Safhi; Fahad Y. Sabei; Mohammed Alissa; Abdulmohsin J. Alamoudi (MDPI AG, 2023)
Mucoadhesive nanosized crystalline aggregates (NCs) can be delivered by the gastrointestinal, nasal, or pulmonary route to improve retention at particular sites. Itopride hydrochloride (ITH) was selected as a drug candidate due to its absorption from the upper gastrointestinal tract. For drug localization and target-specific actions, mucoadhesive polymers are essential. The current work aimed to use second-generation mucoadhesive polymers (i.e., thiolated polymers) to enhance mucoadhesive characteristics. An ITH-NC formulation was enhanced using response surface methodology. Concentrations of Tween 80 and Polyvinyl pyrrolidone (PVP K-30) were selected as independent variables that could optimize the formulation to obtain the desired entrapment efficacy and particle size/diameter. It was found that a formulation prepared using Tween 80 at a concentration of 2.55% and PVP K-30 at 2% could accomplish the goals for which an optimized formulation was needed. Either xanthan gum (XG) or thiolated xanthan gum (TXG) was added to the optimized formulation to determine how they affected the mucoadhesive properties of the formulation. Studies demonstrated that there was an initial burst release of ITH from the ITH/NC/XG and ITH/NC/TXG in the early hours and then a steady release for 24 h. As anticipated, the TXG formulation had a better mucin interaction, and this was needed to ensure that the drug was distributed to tissues that produce mucus. Finally, at the measured concentrations, the ITH/NC showed minimal cytotoxicity against lung cells, indicating that it may have potential for additional in vivo research. The enhanced bioavailability and mean residence time of the designed mucoadhesive NC formulations were confirmed by pharmacokinetic studies.